The Pole & other stories - Coetzee, J. M. 1940- (Harvill Secker, 2023)
"After his piano recital in Barcelona, Witold Walczykiewicz - white-haired virtuoso, controversial interpreter of Chopin - becomes infatuated with Beatriz, stylish patron of the arts and his designated companion at dinner. She does not return his affections - at least at first. She is married, but it's more than that. With astounding persistence he sends her music, letters, poetry, invitations to travel. Somewhat against her will, but also on her terms, she finds herself exploring his world. Is their affair an exercise in control, or a dream of love forced into life? Haunting, crystalline, lit with wry humour, 'The Pole' heads a masterful new collection of short works from one of our very finest writers."
Keywords: Fiktionale Darstellung